Some sources of music in Western Sudan from 1300-1700 - Erlmann, Veit (International Library of African Music, 1973)
African music seems to be still viewed as being without history, at least when judged by the attention paid to this aspect of it. It is only recently that a few scholars have directed their interest to the study of African music in the 19th century. The history of music in Africa in 'mediaeval' times gives rise to even more questions. Though we are furnished with a fairly complete knowledge of 'mediaeval' West Africa in almost all its aspects by Arabian and Sudanese contemporaries of the time, few scholars contributed to the exploration of these early sources
Keywords: African Music; Western Sudan